PENGARUH ADULT ATTACHMENT STYLE TERHADAP KEPUASAN PERNIKAHAN PADA DEWASA AWAL - Sherly Sherly; Denrich Suryadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Relationships with other people are one of the most important things in one’s life. Young adults who are in the phase of forming intimate relationships with others tend to develop romantic relationships and get married. In marriage, marital satisfaction can affect one's life both positively and negatively. Therefore, this study wanted to find what factors could affect marital satisfaction. This study aims to determine whether there is an effect of adult attachment style on marital satisfaction in early adulthood. This study aims to discover the effect of young adults’ adult attachment style on marital satisfaction. This study was conducted on 161 married young adults with children in the age range of 20-40 years old. Moreover, this research is quantitative research by giving a questionnaire that was shared online. The instruments used for this research are Experiences in Close Relationships-Revised (ECR-R) and ENRICH Marital Satisfaction Scale (EMS). The results of this research indicate that anxiety attachment and avoidance attachment have negative impacts on internet addiction (F=83.489, t = -2.630 for anxiety attachment and t= -10.139 for avoidance attachment, p < 0.05). The effect of anxiety attachment and avoidance attachment on marital satisfaction is 51.4%. This effect indicated that individuals with high anxiety attachment or avoidance attachment had a lower level of marital satisfaction.